Environmental Education in Tlaxcala, Mexico, High Schools from a Gender Perspective - Adelina Espejel-Rodríguez; Aurelia Flores-Hernández; Isabel Castillo-Ramos (Revista Electrónica Educare)
This paper is aimed at describing how students, based on their gender, innovate actions in favor of the environment, in order to recover their role in the promotion of environmental education, as well as the activities that motivate them and that they like to maintain their school. The research is conducted within a qualitative methodology framework, with a sample of 80 male and female high school students.  The information is collected using direct observation, questionnaires, and students’ opinions and is later systematized and processes for analysis and interpretation using a descriptive methodology. Results show differences and preferences between genders to innovate and mitigate problems, as well as differences in the reasoning and enthusiasm to perform environmental actions. One of the conclusions is that that women like to take care of the environment more than men since they show more interest in preserving it.